Sleep differences in the UK between 1974 and 2015: insights from detailed time diaries - Lamote de Grignon Pérez, J; Gershuny, J; Russell Foster; De Vos, M (Wiley, 2018)
It is often stated that sleep deprivation is on the rise, with work suggested as a main cause. However, the evidence for increasing sleep deprivation comes from surveys using habitual sleep questions. An alternative source of information regarding sleep behaviour is time-use studies. This paper investigates changes in sleep time in the UK using the two British time-use studies that allow measuring "time in bed not asleep" separately from "actual sleep time". Based upon the studies presented here, people in the UK sleep today 43 min more than they did in the 1970s because they go to bed earlier (~30 min) and they wake up later (~15 min). The change in sleep duration is driven by night sleep and it is homogeneously distributed across the week. The former results apply to men and women alike, and to individuals of all ages and employment status, including employed individuals, the presumed major victims of the sleep deprivation epidemic and the 24/7 society. In fact, employed individuals have experienced a reduction in short sleeping of almost 4 percentage points, from 14.9% to 11.0%. There has also been a reduction of 15 percentage points in the amount of conflict between workers work time and their sleep time, as measured by the proportion of workers that do some work within their "ideal sleep window" (as defined by their own chronotype).